Content marketing and brand engagement on social media: a study of Facebook´s posts in the ecommerce industry in Brazil - Ferrari, Victor Candeloro (2016)
Content marketing refers to marketing format that involves the creation and sharing of media and publishing content in order to acquire customers. It is focused not on selling, but on communicating with customers and prospects. In today world´s, a trend has been seen in brands becoming publishers in order to keep up with their competition and more importantly to keep their base of fans and followers. Content Marketing is making companies to engage consumers by publishing engaging and value-filled content. This study aims to investigate if there is a link between brand engagement and Facebook Content Marketing practices in the e-commerce industry in Brazil. Based on the literature review, this study defines brand engagement on Facebook as the numbers of 'likes' 'comments' and 'shares' that a company receives from its fans. These actions reflect the popularity of the brand post and leads to engagement. The author defines a scale where levels of Content Marketing practices are developed in order to analyze brand posts on Facebook of an ecommerce company in Brazil. The findings reveal that the most important criterion for the company is the one regarding the picture of the post, where it examines whether the photo content is appealing to the audience. Moreover, it was perceived that the higher the level of these criterion in a post, the greater the number of likes, comments and shares the post receives. The time when a post is published does not present a significant role in determining customer engagement and the most important factor within a publication is to reach the maximum level in the Content Marketing Scale.